Development of special clothes for the protection from X-ray radiation - Kozhushko, R. (Theory and practice of design, 2015)
The article is dedicated to the issues of development of special clothes for the protection from X-ray radiation, that are maximally comply with exploitation norms. On the basis of complex research improved construction and technology of making of protective double-sided apron is offered for the personnel of interventional radiology, and its experimental sample is made.